IMPLEMENTATION OF THE BENCHMARKING GUIDELINES ON COMMUNITY PHARMACIES IN MALAYSIA - JENNIFER TAN SEE HUI (Malaysian Journal of Pharmaceutical Sciences, 2008)
The International Pharmaceutical Federation (FIP) adopted a set of Good Pharmacy Practice (GPP) guidelines in 1993 and recommended that the regulatory bodies of individual countries should adapt the guidelines in accordance with their resources. The Malaysian Pharmaceutical Society (MPS) introduced its benchmarking guidelines (BMG) in 2003 as a means to raise the professional standards of the community pharmacy practice in Malaysia. Therefore, this study aimed to determine the extent to which community pharmacies have adopted the BMG. A cross-sectional study was conducted using mail questionnaires, which were posted to all community pharmacies in Malaysia. A total of 371 questionnaires (29.2%) were returned. Only 51.0% of the respondents were aware of the BMG. The extent of compliance with the guidelines was 62.6+21.1% (mean + standard deviation), with a median of 65%. The type and ownership of the community pharmacies were significantly associated with compliance with certain aspects of the guidelines. The main problem in complying with the BMG was financial constraint, and this problem was more likely to occur with independent than with chain pharmacies. However, the respondents generally agreed that most aspects of the BMG could be achieved in less than five years. Since the level of awareness among community pharmacists regarding the BMG is low, the MPS should promote or publicise the BMG further. The BMG should be reviewed before being used as part of the criteria for the accreditation of community pharmacies, as proposed by the MPS to further improve the quality and standards of community pharmacies in Malaysia.